Spin-valve effects in point contacts to exchange biased Сo40Fe40B20 films: III Международный семинар по микроконтактной спектроскопииХарьков, Украина, 8–11 сентября 2014 г. - Balkashin, O.P.; Fisun, V.V.; Triputen, L.Yu.; Andersson, S.; Korenivski, V.; Naidyuk, Yu.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Nonlinear current-voltage characteristics and magnetoresistance of point contacts between a normal metal (N) and films of amorphous ferromagnet (F) Сo40Fe40B20 of different thickness, exchange-biased by antiferromagnetic Mn80Ir20 are studied. A surface spin valve effect in the conductance of such F–N contacts is observed. The effect of exchange bias is found to be inversely proportional to the Сo40Fe40B20 film thickness. This behavior as well as other magneto-transport effects we observe on single exchange-pinned ferromagnetic films are similar in nature to those found in conventional three-layer spin-valves.